Evaluating the Sensitivity and Specificity of Promising Circulating Biomarkers to Diagnose Liver Injury in Humans. (23rd January 2021) - Llewellyn, Heather P; Vaidya, Vishal S; Wang, Zhenyu; Peng, Qinghai; Hyde, Craig; Potter, David; Wang, Jianying; Zong, Qing; Arat, Seda; Martin, Matt; Masek-Hammerman, Katherine; Warner, Roscoe; et al.
Abstract: Early diagnosis of drug-induced liver injury (DILI) continues to be a major hurdle during drug development and postmarketing. The objective of this study was to evaluate the diagnostic performance of promising biomarkers of liver injury—glutamate dehydrogenase (GLDH), cytokeratin-18 (K18), caspase-cleaved K18 (ccK18), osteopontin (OPN), macrophage colony-stimulating factor (MCSF), MCSF receptor (MCSFR), and microRNA-122 (miR-122) in comparison to the traditional biomarker alanine aminotransferase (ALT). Biomarkers were evaluated individually and as a multivariate model in a cohort of acetaminophen overdose ( n  = 175) subjects and were further tested in cohorts of healthy adults ( n  = 135), patients with liver damage from various causes ( n  = 104), and patients with damage to the muscle ( n  = 74), kidney ( n  = 40), gastrointestinal tract ( n  = 37), and pancreas ( n  = 34). In the acetaminophen cohort, a multivariate model with GLDH, K18, and miR-122 was able to detect DILI more accurately than individual biomarkers alone. Furthermore, the three-biomarker model could accurately predict patients with liver injury compared with healthy volunteers or patients with damage to muscle, pancreas, gastrointestinal tract, and kidney. Expression of K18, GLDH, and miR-122 was evaluated using a database of transcriptomic profiles across multiple tissues/organs in humans and rats. K18 mRNA ( Krt18 ) and MiR-122 were highly expressed in liver whereas GLDH mRNA ( Glud1 ) was widely expressed. We performed a comprehensive, comparative performance assessment of 7 promising biomarkers and demonstrated that a 3-biomarker multivariate model can accurately detect liver injury.